2014
DOI: 10.1063/1.4875102
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Brillouin gain spectrum in tapered polymer optical fiber

Abstract: We report on the first observation of the Brillouin gain spectrum in a perfluorinated graded-index polymer optical fiber (POF) tapered by a heat-and-pull technique. The Stokes power was slightly enhanced by tapering probably on account of higher optical power density in the core. In addition, the Brillouin frequency shift was decreased by $40 MHz, which was experimentally verified to be partially caused by high heating temperature applied to the POF during the taper fabrication process. We anticipate that our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…To tackle this problem, strain and temperature sensors using polymer optical fibers (POFs) [11] have attracted a lot of attention, because POFs are so flexible that they can withstand larger strain of several tens of percent (even 100% [12]). To date, various strain and temperature sensors using POFs have been developed, including those based on fiber Bragg gratings [13,14], modal interference [15][16][17], Brillouin scattering [18][19][20][21][22][23][24][25], and Rayleigh scattering [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To tackle this problem, strain and temperature sensors using polymer optical fibers (POFs) [11] have attracted a lot of attention, because POFs are so flexible that they can withstand larger strain of several tens of percent (even 100% [12]). To date, various strain and temperature sensors using POFs have been developed, including those based on fiber Bragg gratings [13,14], modal interference [15][16][17], Brillouin scattering [18][19][20][21][22][23][24][25], and Rayleigh scattering [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The loss is reported to increase with increasing temperature [25,26], and especially at high temperature of >100°C, irreversible loss has been observed [25,26]. In addition, we have recently found that, when a POF sample is heated at such high temperature and then cooled to room temperature, its Brillouin frequency shift (BFS) does not return to the initial value at room temperature [22]. These results suggest the existence of a useful "thermal memory effect" of POFs, on the detail of which no report has been provided yet.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, here, we focus on the use of long tapered PFGI-POFs, which can enhance the Stokes power (generated at the tapered section), because the optical power density at the core center increases. 25) To date, many kinds of tapering techniques have been demonstrated. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Among them, what we call a heat-andpull technique has been most widely used to taper optical fibers, including glass fibers, [26][27][28][29][30][31][32] PMMA-POFs, 33,34) and PFGI-POFs.…”
mentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Among them, what we call a heat-andpull technique has been most widely used to taper optical fibers, including glass fibers, [26][27][28][29][30][31][32] PMMA-POFs, 33,34) and PFGI-POFs. 25,[35][36][37] Many kinds of heat sources have been used for heating fibers, including a flame, [25][26][27][28][29] a CO 2 laser, 30) a compact furnace, 31,[33][34][35][36] a fusion splicer, 32) and a solder gun, 37) but these are sometimes not easy to handle, prepare, or control. To overcome this inconvenience in tapering POFs, hot water appears to be a good candidate as a heat source, because the glass-transition temperature of POFs is relatively low (∼100°C).…”
mentioning
confidence: 99%
“…21) We anticipate that the use of tapered PFGI-POFs is also one of the promising methods for enhancing the Brillouin signal (generated at the tapered section), as the optical power is more concentrated at the core center. 22) The so-called heat-and-pull technique is most commonly used to taper optical fibers, and has been applied not only to glass fibers [23][24][25][26][27][28][29] but also to PMMA-POFs 30,31) and PFGI-POFs. 22,[32][33][34] However, external heat sources, such as a flame, [22][23][24][25][26] a CO 2 laser, 27) a compact furnace, 28,[30][31][32][33] a solder gun, 34) and a fusion splicer, 29) must be prepared, leading to handling difficulty and=or inconvenience.…”
mentioning
confidence: 99%